Kerman Health System Workers Knowledge and AttitudesRegarding the Spontaneous Reporting System forAdverse Drug Reactions: ADR reporting by health system workers - Seyed Mojtaba Sohrevardi; Mahmood Reza Heidari (Iranian Journal of Pharmaceutical Sciences, 2009)
Adverse drug reaction (ADR) is one of the most life threatening problems, and the economic burden of ADR is considerable. The main objective of this study was to assess the attitude of the Kerman health system staff, to evaluate their knowledge of the spontaneous reporting system and to identify the reasons for low reporting rate. In this descriptive study, a Persian translated questioner was used based on standard European pharmacovigilance research group. Among 800 distributed questionnaires, 78% were filled and returned. Returned questioner (82%) indicated to have already suspected an ADR but only 4% reported it to Iranian ADR centre.The 4 major reasons for not reporting were: a) reporting process was unknown (65%),b) Iranian pharmacovigilance centre was unknown for the staff (45%), c) the yellow cards for reporting ADR were not available (30%), and d) ADR were not important (22%). We concluded that our medical staff’s knowledge about ADR is little. Appropriate teaching and acceptable effort is needed to strengthen the current system and to prevent other serious ADRs.